Novel deproteinized natural rubber latex adhesive used in extraoral maxillofacial prostheses - Paweena Kongkon,; Wiwat Pichayakorn,; Sasiwimol Sanohkan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aimed to develop an adhesive for silicone maxillofacial prostheses and compared the properties with the Daro adhesive hydrobond (Factor II, Inc, Lakeside, AZ, USA). Two adhesives were developed from non-vulcanized natural rubber-based adhesives (Adhesive A) and deproteinized natural rubber latex (DNRL) products (Adhesive B) and stored at 4 °C. The Control group was the commercial Daro adhesive hydrobond (Factor II, Inc, Lakeside, AZ, USA). The physical properties (appearance, viscosity, spreadability, color, and pH) of the adhesives were measured and every week for 12 weeks after storing at 4 °C. The adhesives were characterized under scanning electron microscopy. Mechanical testing done were peel bond strength and biocompatibility testing was done using MTT assay. Physical, surface, and mechanical properties were compared with the commercial adhesive. Data analysis was done using SPSS version 24. Both adhesives were physically and chemically stable at temperature 4 °C and had suitable peel bond strength adhesives as the commercial adhesive. Hence, the adhesives can be used to adhere to the maxillofacial silicone prostheses.